Disruption of regulatory mechanisms as a stress factor for patients with metabolic syndrome - I. A. Gribanov; E. G. Zarubina (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Introduction. Throughout history, humanity has lived and developed in accordance with its biological rhythms, which provided the adaptation of the body to the factors of external and internal environment, ensuring the normal synchronous functioning of all its components.The purpose of this work was to study the stressful influence of circadian rhythms disturbance on patients with metabolic syndrome (MS) under conditions of dark deprivation.Material and methods of investigation. We selected patients with MS and disturbed circadian rhythms – a total of 102 people (all men) from among those who constantly work at night, in whom a decrease in melatonin levels was recorded at the preliminary stage. According to the set objectives, 102 patients (young age according to WHO criteria) were divided into three groups of 33, 37 and 32 persons according to the criterion "duration of influence of dark deprivation and MS history duration": 0–5, 5–10 and over 10 years. In the first group the mean age was 30.1 ± 1.4 years, in the second group – 36.5 ± 1.5 years, in the third group the mean age did not exceed 40.3 ± 0.9 years. Melatonin levels (as confirmation of circadian rhythm disturbances) in blood serum were studied in all study participants using Melatonin ELISA immunoassay kit (IBL, Germany). Results and discussion. Normally, when blood cortisol is measured before 10 a.m., its average value varies in a wide range from138 to 635 nmol/l. The increase up to 700 nmol/l is admitted, which is regarded as a negative influence of external factors during the examination. However, one should keep in mind that during evening measurements, cortisol levels in men may normally decrease to 80 nmol/l.Conclusions. Thus, dark deprivation in patients with metabolic syndrome leads to the formation of a stress response. Maximum changes occur after 10 years of disturbance of regulatory mechanisms and lead to a pronounced imbalance between the sympathetic and parasympathetic nervous system, increased vascular tone and changes in the profile of blood pressure during the day towards the predominance of Non-dippers and Night-peers, which increases the risk of progression of metabolic syndrome symptoms.